2018
DOI: 10.1002/jcp.26890
|View full text |Cite
|
Sign up to set email alerts
|

TULA‐family proteins: Jacks of many trades and then some

Abstract: UBASH3/STS/TULA is a novel two-member family, which exerts several key regulatory effects in multiple cell types. UBASH3B/STS-1/TULA-2 is a highly active protein tyrosine phosphatase; its major target appears to be a specific regulatory site of protein tyrosine kinases of the Syk family, dephosphorylation of which inhibits Syk and Zap-70 kinases and suppresses receptor signaling mediated by these kinases. UBASH3A/STS-2/TULA exhibits substantial homology to UBASH3B/STS-1/TULA-2, but possesses only a small fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 95 publications
1
17
0
Order By: Relevance
“…The mammalian ortholog of CG4025 (DRAM1/2) is induced by p53 in response to DNA damage and promotes apoptosis and autophagy (Guan et al, 2015). The mammalian orthologs of CG13604 (UBASH3A/B) are tyrosine phosphatases that repress SYK kinase, an enzyme reported to help protect cells against ROS, with superoxide activation of Drosophila Syk kinase signalling tissue injury (Secchi et al, 2015; Srinivasan et al, 2016; Tsygankov, 2018). Finally, the ortholog of CG3709 in archaea has tRNA pseudouridine synthase activity, but the human ortholog PUS10 has been reported to be cleaved during apoptosis and promote caspase-3 activity, thus its loss may slow apopotic cell death (Jana et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The mammalian ortholog of CG4025 (DRAM1/2) is induced by p53 in response to DNA damage and promotes apoptosis and autophagy (Guan et al, 2015). The mammalian orthologs of CG13604 (UBASH3A/B) are tyrosine phosphatases that repress SYK kinase, an enzyme reported to help protect cells against ROS, with superoxide activation of Drosophila Syk kinase signalling tissue injury (Secchi et al, 2015; Srinivasan et al, 2016; Tsygankov, 2018). Finally, the ortholog of CG3709 in archaea has tRNA pseudouridine synthase activity, but the human ortholog PUS10 has been reported to be cleaved during apoptosis and promote caspase-3 activity, thus its loss may slow apopotic cell death (Jana et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Gene-level FPKM (fragments per kilobase of gene per million read pairs) were extracted from the gene abundance output files produced by StringTie and merged into a gene expression matrix (GEM) using a PBS-GEM Perl script. The matrix was log 2 transformed and preprocessed using the preprocessCore R library (Tsygankov, 2018) to detect outliers and reduce technical noise. Pairwise Kolmogorov-Smirnov (KS) tests were performed to test for outlier samples (KS Dval > 0.15).…”
Section: Methodsmentioning
confidence: 99%
“…Ubiquitin associated and SH3 domain containing A (UBASH3A) gene is mapped to chromosome 21q22.3 [35]. Its expression is thought to be restricted to lymphoid tissues and primarily T cells [36].…”
Section: Introductionmentioning
confidence: 99%
“…Its expression is thought to be restricted to lymphoid tissues and primarily T cells [36]. Genetic studies on mouse models revealed that simultaneous deletion of Ubash3a and Ubash3b causes hyperreactivity of T cells due to their involvement in the regulation of protein tyrosine kinase-mediated signaling [35]. UBASH3A participates in pro-apoptotic pathways by binding to AIF independently of caspase apoptotic events [37].…”
Section: Introductionmentioning
confidence: 99%